Finite Rank Solution for Conformable Degenerate First-Order Abstract Cauchy Problem in Hilbert Spaces (European Journal of Pure and Applied Mathematics, 2021)
In this paper, we find a solution of finite rank form of fractional Abstract Cauchy Problem. The fractional derivative used is the Conformable derivative. The main idea of the proofs are based on theory of tensor product of Banach spaces.
Keywords: Tensor product of Banach spaces; finite rank function; conformable derivative; abstract Cauchy problem.